A Study about Awareness of Anger Management, Aggressiveness and Anger Expression Tendency of Undergraduate Students: Focusing on Comparing Students of Health and Physical Education Major to Non-Major Students - Shimofure, Tomonori; Kiyama, Keiko (Kitakanto Journal of Physical Education, Health and Sport Sciences, 2017)
The purpose of this study was to gain knowledge that serves as a basis for proposing anger management to students of health and physical education major (hereinafter, referred to as P.E. majors) through investigation of their awareness about anger management, aggressiveness and anger expression tendency. Subjects were students of P.E. majors and their non-major counterparts (Faculty of Education other than Health and physical Education Major, Faculty of Science and Technology, Faculty of Social Information, Faculty of Medicine), of a National University in Kanto. Some results of the comparison are summarized as follows: a) About aggressiveness, Male P.E. students are prone to physical attack while female P.E. students are prone to verbal attack. b) About anger tendency, P.E. students both sexes were prone to attack and get angry when they were attacked by other people. In addition to preventing them from behavioral problems such as delivering corporal punishment when they become teachers, teaching anger management to P.E. majors is significant as they could also teach it to their students at P.E. classes. In the future, further investigation and research is necessary as to how to develop the education of anger management in health and physical education. The ultimate goal is to make anger management a part of the curriculum.